Smart Aquarium Design Using Raspberry Pi and Android Based - Khairunisa Khairunisa; Mardeni Mardeni; Yuda Irawan (Journal of Robotics and Control (JRC), 2021)
For aquarium owners, sometimes their daily activities are busy with other busy activities was studied by nusantara[1]. With this density of activity it often makes it difficult for fish aquarium owners to provide fish with the feeding process, which is usually done manually when at home was studied by pasha[2]. From this problem, a smart aquarium device was designed to feed aquaculture fish automatically, namely Smart Aquarium Design Using Android-Based Raspberry Pi, designed to provide convenience in the process of maintaining fish in an aquarium. This aquarium can perform several actions such as fish feeding automatically can be done using Android via the internet network and control the aquarium decorative lights. To move the fish feeding valve, it uses a servo motor to drive the fish feeding valve and also uses a relay as an on / off aquarium decorative light. Fish feed machines can feed fish on a scheduled basis if the user forgets to feed fish. Smart aquarium is also equipped with a water filter so that aquarium water does not need to change water.